Bordeaux mixture and Diabrotica speciosa adults extract effect on plant sanitary management in common bean grown under organic crop system (Revista de Ciências Agroveterinárias, 2012)
The occurrence of insect pests is one of the major causes of low yields and inconstant levels of production of common bean crops. The organic production systems do not allow the use of synthetic chemical substances to manage insect pests. The objective of this work was to evaluate the repellent effect of Bordeaux mixture and fresh extract of Diabrotica speciosa adults against the main herbivorous Coleopterans species associated to organic common bean crops on the incidence of fungal diseases, the toxicity of copper and the bean grain production. The experiments were carried out at an agroecological area located in Rio do Sul, district of Santa Catarina State, during the first and second bean crop season (summer 2004/05). Each experiment was carried out in a completely randomized design with seven treatments and four replications. The replications consisted of nine rows of common bean plants at a 12 square meter area. The Bordeaux mixture was tested at the concentrations 0.15, 0.30, 0.50 and 1.00% and the fresh D. speciosa extract was tested at the concentrations 800 and 1600 insects ha-1. No substance was applied to the control replicates. The weekly treatments began when bean plants had 50% of the first definitive leaf expanded and lasted until the beginning of the flowering period. In both experiments, the assessment of herbivorous coleopteran species was carried out daily by means of the ground cloth method. The percentage of D. speciosa adults collected was 4.7 and 55.92% of the total amount of leaf eating coleopterans captured, respectively, in the first and second harvest. The data did not show significant differences in the substances tested, neither between the tested concentration, nor between the treatments and the control. The grain production did not differ between the treatments. Bordeaux mixture and fresh D. speciosa extract did not repel the bean leaf eating coleopterans species assessed. At the concentration of 1.00% Bordeaux mixture caused fitotoxicity on bean leaves.
Keywords: agroecology; bordeaux mixture; organic agriculture; insect.